Information and performance optimization: a study of Indian IPOs during 2005-2012. Issue 4 (7th November 2017) - Chhabra, Sheena; Kiran, Ravi; Sah, A.N.; Sharma, Vikas
Abstract : Purpose: The purpose of this paper is to focus on examining the first day returns of initial public offerings (IPOs) and the role of information on their performance. The study tries to optimize the returns of the new issues during 2005-2012 with risk as a constraint. Design/methodology/approach: The initial returns are measured through the market-adjusted excess return and the risk associated with the new issue is measured through underwriters' reputation. The returns have been optimized through a mixed integer linear problem using the Maple software. Findings: The previous studies show that various informational variables affect the listing day returns significantly. The results of the present study indicate that the mean of initial returns for IPOs during 2005-2012 is 18.03 and the mean risk for these issues is 0.46. The findings also suggest that the optimal returns are obtained in the pre-recession era (2005-2008) and the value for the same is 50.02 percent. Originality/value: The current study contributes in the investment decisions for global investors as every investor wants to maximize his/her returns. The optimal returns with risk as a constraint will help the investors in improving their investment decision as a prudent investor does not aim solely at maximizing the expected return of an investment but is also interested in optimizing with the minimization of risk.